Overview of Buying and Selling in Islam - Zamaluddin; Mubarok, Abdullah; Bahri, Efri Syamsul (Journal of Multi-Disciplines Science, 2023)
Buying and selling is a daily activity of the global community. This study aims to review buying and selling in Islam. This study uses a qualitative method. Descriptive research approach and literature review. Data obtained from reference journals. The results of this study explain the definition of buying and selling and buying and selling based on Sharia. The practice of buying and selling is explained in the Qur'an in Surah Al-Baqarah verse 275, which mentions leaving usury and buying and selling legally. Every Muslim needs to pay attention to the Sharia-based buying and selling mechanism.